2020
DOI: 10.3390/molecules25245877
|View full text |Cite
|
Sign up to set email alerts
|

The Intestinal Efflux Transporter Inhibition Activity of Xanthones from Mangosteen Pericarp: An In Silico, In Vitro and Ex Vivo Approach

Abstract: The capacity of α-mangostin (α-MG) and β-mangostin (β-MG) from mangosteen pericarp on P-glycoprotein (Pgp) in silico, in vitro, and ex vivo was investigated in this study. Screening with the ADMET Predictor™ program predicted the two compounds to be both a Pgp inhibitor and Pgp substrate. The compounds tended to interact with Pgp and inhibit Pgp ATPase activity. Additionally, bidirectional transport on Caco-2 cell monolayers demonstrated a significantly lower efflux ratio than that of the control (α-(44.68) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Spieler et al [60] reported that donepezil concentration in the brain and the cerebrum to plasma ratio of donepezil were increased in P-glycoprotein (P-gp) deficient mice compared to control, indicating that the brain bioavailability of donepezil depends on P-gp. Considering that numerous reports the inhibitory effects of mangosteen pericarp extract and xanthones as main components of mangosteen pericarp extract against P-gp [61,62], the increased donepezil concentration in the brain may be due to the inhibition of P-gp-mediated donepezil efflux through BBB by WMP. Although P-gp is expressed in many other organs, the degree of P-gp inhibition by P-gp inhibitors are different because the concentrations of P-gp inhibitor in the specific tissue are various, with different inhibiting P-gp activities [61,63,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spieler et al [60] reported that donepezil concentration in the brain and the cerebrum to plasma ratio of donepezil were increased in P-glycoprotein (P-gp) deficient mice compared to control, indicating that the brain bioavailability of donepezil depends on P-gp. Considering that numerous reports the inhibitory effects of mangosteen pericarp extract and xanthones as main components of mangosteen pericarp extract against P-gp [61,62], the increased donepezil concentration in the brain may be due to the inhibition of P-gp-mediated donepezil efflux through BBB by WMP. Although P-gp is expressed in many other organs, the degree of P-gp inhibition by P-gp inhibitors are different because the concentrations of P-gp inhibitor in the specific tissue are various, with different inhibiting P-gp activities [61,63,64].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that numerous reports the inhibitory effects of mangosteen pericarp extract and xanthones as main components of mangosteen pericarp extract against P-gp [61,62], the increased donepezil concentration in the brain may be due to the inhibition of P-gp-mediated donepezil efflux through BBB by WMP. Although P-gp is expressed in many other organs, the degree of P-gp inhibition by P-gp inhibitors are different because the concentrations of P-gp inhibitor in the specific tissue are various, with different inhibiting P-gp activities [61,63,64]. In this view, WMP might significantly inhibit only P-gp mediated donepezil efflux through BBB, not in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal transporter proteins and metabolizing enzymes work together and have crucial roles in regulating the oral absorption of various xenobiotics. In Caco-2 cell monolayers, the transporter proteins, efflux proteins, and metabolic phase II conjugation enzymes are available [29][30][31]. Moreover, the Caco-2 cell model can be used to determine the transport mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…GGA GCC CCA GGA AAC ATT G-3' 5'-CAT AAC TAG CGC CTT GCA C-3ATG GAA ATA CAA CAA ACA CAC-3' 5'-CTG CTT GAA TGC GCC AAA C-3CTC CAA GGA GTA AGA CC-3′ 5′-CCC CTC TTC AAG GGG TCT AC-3′157[31] …”
mentioning
confidence: 99%
“…AAT ACA CCA ACG CCT CCA AG-3' 5'-TTG TTG CCG CTT TTG CTC TC-3ATG GAA ATA CAA CAA ACA CAC-3' 5'-CTG CTT GAA TGC GCC AAAC-3GGT CAA AAT GCG GTC ATG G-3' 5'-CCA TTG GTA CCT GTA GAA AC-GGA GCC CCA GGA AAC ATT G-3' 5'-CAT AAC TAG CGC CTT GCA C-3ATG GAA ATA CAA CAA ACA CAC-3' 5'-CTG CTT GAA TGC GCC AAA C-3CTC CAA GGA GTA AGA CC-3′5′-CCC CTC TTC AAG GGG TCT AC-3′ 157[31] …”
mentioning
confidence: 99%